Reduced magnitude and shifted seasonality of CO2 sink by experimental warming in a coastal wetland. Issue 2 (30th November 2020) - Sun, Baoyu; Yan, Liming; Jiang, Ming; Li, Xinge; Han, Guangxuan; Xia, Jianyang
Abstract: Coastal wetlands have the highest carbon sequestration rate per unit area among all unmanaged natural ecosystems. However, how the magnitude and seasonality of the CO2 sink in coastal wetlands will respond to future climate warming remains unclear. Here, based on measurements of ecosystem CO2 fluxes in a field experiment in the Yellow River Delta, we found that experimental warming (i.e., a 2.4°C increase in soil temperature) reduced net ecosystem productivity (NEP) by 23.7% across two growing seasons of 2017–2018. Such a reduction in NEP resulted from the greater decrease in gross primary productivity (GPP) than ecosystem respiration (ER) under warming. The negative warming effect on NEP mainly occurred in summer (−43.9%) but not in autumn (+61.3%), leading to a shifted NEP seasonality under warming. Further analyses showed that the warming effects on ecosystem CO2 exchange were mainly controlled by soil salinity and its corresponding impacts on species composition. For example, warming increased soil salinity (+35.0%), reduced total aboveground biomass (−9.9%), and benefited the growth of plant species with high salt tolerance and late peak growth. To the best of our knowledge, this study provides the first experimental evidence on the reduced magnitude and shifted seasonality of CO2 exchange under climate warming in coastal wetlands. These findings underscore the high vulnerability of wetland CO2 sink in coastal regions under future climate change.